Chemical Characterization of Hot Trub and Residual Yeast: Exploring Beer By-Products for Future Sustainable Agricultural Applications - Laura Alessandroni; Riccardo Marconi; Marco Zannotti; Stefano Ferraro; Tereza Dolezalova; Diletta Piatti; Ghazal Namazzadeh; Simone Angeloni; Gianni Sagratini (Foods, 2025)
Three types of solid waste are produced during beer fermentation: spent grain, hot trub, and residual yeast. While the first is used as livestock feed, the seconds has not yet found any real reapplication in the field of circular economy. The aim of this work is to study and characterize these two brewing wastes, i.e., hot trub and residual yeast, to evaluate their potential reuse in the agricultural field. Samples from top-fermented and bottom-fermented beers were chemically investigated. Initially, the safety was assessed via multi-detection analysis of 57 mycotoxins, and all samples were deemed safe. Subsequently, the chemical and elemental composition was examined via ICP-MS and microanalysis, along with phenolic compounds and antioxidant activity via HPLC and spectrophotometric determinations, to achieve a thorough characterization of these waste samples. The C/N ratio of residual yeast from top-fermented beer and hot trub of the bottom-fermented one were near the optimal one (10:1). This research marks an initial step towards repurposing brewery waste materials as fertilizers. The subsequent steps will involve the formulation and field trials.